Grassroots-Based Curriculum Innovation: Integrating Research into Local Content Subjects in the Implementation of the Independent Curriculum - Suratman; Sugiyono (Pascasarjana Universitas Mataram, 2026)
Grassroots-based curriculum innovation through integration into local content subjects is crucial in the implementation of the Merdeka curriculum. As a pilot project madrasah, consistency in curriculum development that integrates research is essential. This training aims to describe teachers' perceptions and experiences in research-based implementation, their active involvement in designing solutions for integrating research into local content subjects, analyze the impact of teacher participation in the training process, and outline the real challenges teachers face in developing a research-based curriculum. The community service method uses PAR, which consists of the stages: to know, to understand, to plan, to act, and to change. The training participants consisted of the Head of Madrasah Education, the Principal, the Deputy Principal, and 25 teachers. Based on the training results, the teachers successfully developed a semester program as a mapping of research material, a research syllabus integrated with the love-based curriculum, a lesson plan, and student worksheets with different themes. The training participants, including teachers outside the pilot project, were very enthusiastic and produced a set of learning curricula and actively participated in overcoming obstacles in the process of developing research curriculum documents for local content subjects. In this way, grassroots curriculum innovation can produce a set of learning curricula compiled by teachers for the learning process in local content subjects.